Konsepsi Reformulasi Hierarki PUU Di Indonesia - Kristianus Jimy Pratama (Arena Hukum, 2022)
Law Number 15 of 2019 concerning Amendments to Law Number 12 of 2011 on Legislation Making classify the types of and the hierarchy of laws and regulations in Indonesia. Meanwhile, in its development, the a quo provisions actually lead to an inconsistency when compared to the ideals and formulations of the Constitution. This article aims to describe the building of legal arguments related to the opportunity to reformulate the types and hierarchies of laws and regulations in Indonesia and the implications of their application. This of normative legal research uses statutory and comparative law approach. The results are that the types and hierarchies of legislation in a country are closely related to the legal system adopted in accordance with the ideals of each basic legal norm in the country and to meet the needs of the community for the rule of law. Therefore, to create legal consistency in each type and hierarchy of laws and regulations in Indonesia, it is necessary to include State Institution Regulations and restore the position of Village Regulations in the hierarchy of laws and regulations.